Tác động của đặc trưng hội đồng quản trị đến hiệu quả tài chính của các công ty cổ phần niêm yết trên thị trường chứng khoán Việt Nam - Chu Thị Thu, Thủy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
The objective of the research is to clarify the impact of characteristics of the board of directors on financial performance of joint-stock companies listed on the Vietnam’s Stock Market. The panel regression is applied in this research with supporting of Stata 14 software. The research sample consists of 654 joint-stock companies over 2016–2018 period. The research pointed out that the characteristics of board of directors affect significantly financial performance of Vietnam’s listing joint-stock companies, where duality and board size have positively significant effects on the financial performance (ROA) at the significant level of 5%; the number of board meetings and the number of independent members of board of directors have negatively significant influences on the financial performance; however, the gender diversity of board of directors has an insignificant relationship to financial performance at the significant level of 5%
Keywords: Board of directors; Joint-stock companies; Vietnam's Stock Market; Financial performance